A two-year longitudinal study of retinal vascular impairment in patients with amnestic mild cognitive impairment - Criscuolo, Chiara; Cennamo, Gilda; Montorio, Daniela; Carotenuto, Antonio; Migliaccio, Miriana; Moccia, Marcello; Salvatore, Elena; Lanzillo, Roberta; Costagliola, Ciro; Morra, Vincenzo Brescia (Frontiers in Aging Neuroscience, 2022)
Objective To evaluate the relation between retinal vascular impairment and cognitive decline in patients with amnestic mild cognitive impairment (aMCI) over time. Methods Spectral domain-optical coherence tomography (SD-OCT) and OCT angiography study was performed in aMCI patients over 2 years follow-up and compared to baseline. Results Thirty-eight eyes from 19 aMCI patients were evaluated. Structural and vascular OCT measures were reduced at follow-up except for vessel density (VD) of the choriocapillaris, unchanged, and foveal avascular zone, which was increased; no changes in any parameter were found in 18 age-matched healthy controls. Overall, these findings were confirmed when patients were evaluated separately according to progression to dementia. Only non-converters to dementia showed significant VD reduction in the deep capillary plexuses (coeff. β = −4.20; p < 0.001), may be for an initial massive VD depletion becoming less evident with progression of the disease. MMSE reduction was associated with a higher ganglion cell complex reduction (coeff. β = 0.10; p = 0.04) and a higher VD reduction in the radial peripapillary capillary (RPC) plexus (coeff. β = 0.14; p = 0.02) in the whole patient group, while it was associated with a higher VD reduction only in RPC plexus in converters (coeff. β = 0.21; p < 0.001). Conclusion Our data shows vascular impairment progression in the inner retina of aMCI patients and support the hypothesis that vascular changes may contribute to the onset and progression of Alzheimer’s disease. Other follow-up studies, with a larger number of patients, are needed to better define VD as a potential biomarker.